2018
DOI: 10.1055/s-0038-1670687
|View full text |Cite
|
Sign up to set email alerts
|

Management of Facial Nerve Schwannoma: A Multicenter Study of 50 Cases

Abstract: Objective In the management of facial nerve schwannoma (FNS), surgical tumor resection is now often being replaced with more conservative approaches, such as observation with serial imaging or stereotactic radiosurgery (SRS). Given the scarcity of these lesions, determining the optimal management of FNS remains challenging and subject of debate with multiple treatment approaches supported in the literature. Methods A retrospective chart review was performed in two academic centers for patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…If the preoperative House–Brackmann grade is ≥3, total tumor resection and nerve transplant reconstruction are indicated. Similar opinions have been expressed in previous literature [ 16 , 17 ]. The facial nerve function after reconstruction improves as the period of facial nerve paralysis before surgery becomes shorter.…”
Section: Discussionsupporting
confidence: 88%
“…If the preoperative House–Brackmann grade is ≥3, total tumor resection and nerve transplant reconstruction are indicated. Similar opinions have been expressed in previous literature [ 16 , 17 ]. The facial nerve function after reconstruction improves as the period of facial nerve paralysis before surgery becomes shorter.…”
Section: Discussionsupporting
confidence: 88%
“…The main aim is to preserve facial function at the most favorable level for the longest period. Eshraghi et al concluded that wait and watch management results in the best facial nerves outcomes [7]. In patients with favorable facial nerve function (HB<III) and stable tumor size, observation with serial imaging is preferred until the facial nerve function deteriorates.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitations of the MFA include the risk of seizures and possible language impairment in the dominant hemisphere secondary to excessive retraction of the temporal lobe, the difficulty in resecting larger tumors, the narrow surgical corridor offered, and the tight exposure of posterior fossa, which might limit the resection of lesions with a significant cisternal component projecting downwards to the lower CPA floor. The vestibule and the cochlea can be injured during drilling of the bone above the labyrinthine segment of the facial nerve at the lateral part of the IAM [ 1 , 4 , 9 , 10 ].…”
Section: Limitationsmentioning
confidence: 99%